Arachnoid cyst in the quadrigeminal cistern: A case from Afghanistan - Barakatullah Mohammadi; Ahmad Neyazi; Abdul Qadir Qader; Nosaibah Razaqi; Habibah Afzali; Mehrab Neyazi (Radiology Case Reports, 2024)
Arachnoid cysts, fluid-filled lesions within the central nervous system, pose diagnostic challenges. This study examines a unique case of a quadrigeminal arachnoid cyst in a 13-year-old girl, emphasizing accurate identification and treatment. The patient's symptoms of blurred vision and headaches led to the discovery of papilledema and imaging revealing a sizable cyst causing obstructive hydrocephalus. Urgent surgical intervention involved suboccipital craniectomy and infratentorial-supracerebellar cyst drainage, resulting in favorable postoperative outcomes. Further analysis of anatomical variations, age-related factors, and etiological debates deepens understanding. Diagnostic advancements, notably MRI, are crucial for noninvasive characterization. This case offers nuanced insights into managing arachnoid cysts, highlighting the success of tailored surgical strategies. Recognizing clinical subtleties, utilizing diagnostic innovations, and customizing surgical techniques are essential for navigating complexities. This study underscores the importance of a comprehensive approach in addressing the challenges of arachnoid cysts within the central nervous system.